2022
DOI: 10.3389/fonc.2022.1060496
|View full text |Cite
|
Sign up to set email alerts
|

Identifying tumor antigens and immune subtypes of gastrointestinal MALT lymphoma for immunotherapy development

Abstract: MALT lymphoma is an extranodal B-cell lymphoma of the marginal zone of mucosa-associated lymphoid tissue (MALT), caused by malignant transformation of B-cells in the marginal zone. In this work, we aim to explore the potential relationship between MALT lymphoma and DLBCL. Vaccines derived from messenger ribonucleic acid (mRNA) may provide satisfactory results. Despite being a promising treatment option, immunotherapy isn’t widely used in treating renal cell carcinoma, as only a few patients respond to the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In recent years, multiple studies have applied the bioinformatics analysis to evaluate the correlation between environmental toxicity and cancers. As is shown in the previous study, phthalates have been associated with potential negative effects on prostate cancer, and a pharmacological method has been proposed to predict harmful effects ( 27 ). In addition, a former study also discovered that multiple water pollutants were considered to be closely associated with the human diseases, such as colon tumors, breast tumors, hepatitis B, bladder cancer, and human cytomegalovirus infection ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multiple studies have applied the bioinformatics analysis to evaluate the correlation between environmental toxicity and cancers. As is shown in the previous study, phthalates have been associated with potential negative effects on prostate cancer, and a pharmacological method has been proposed to predict harmful effects ( 27 ). In addition, a former study also discovered that multiple water pollutants were considered to be closely associated with the human diseases, such as colon tumors, breast tumors, hepatitis B, bladder cancer, and human cytomegalovirus infection ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, pharmacological techniques and omics databases were used to predict the potentially harmful effects of hazardous substances The effects of dibutyl phthalate on prostate cancer are possibly androgen-independent at low concentrations, so androgen-deprivation therapy patients may be exposed to this chemical ( 20 ). In another study, an online database provided a rationale for mRNA vaccine development and suggested that KLHL14 might serve as an antigen for the development of mRNA vaccines in MALT lymphoma patients ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the different methods used in the bioinformatics analysis may lead to the bias ( 27 ). In addition, the application of the biomarkers in the clinical diagnosis, treatment and diagnosis requires the further validation ( 20 , 21 ). Also, multiple studies are also very important to further validate the role of risk model in the OCSS cohort ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the molecular signatures database (version 7.0), gene sets were retrieved. In order to evaluate potential biological function changes, various samples were evaluated using the GSVA algorithm [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, with the quick development of bioinformatics analysis, in silico analysis has been widely taken into consideration for the analysis of the etiology, prevention, and prognostic prediction [13][14][15]. In this work, the aim is to explore the genes that play a key role in the occurrence of OA.…”
Section: Introductionmentioning
confidence: 99%